Cultural Integration in Adolescent Reproductive Health Promotion Initiatives: Insights from Tengger, Indonesia - Nurlaela Widyarini; Diana Setiyawati; Sofia Retnowati (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
Context significantly influences the effectiveness of adolescent reproductive health (ARH) promotion. Successful efforts to improve ARH quality often overlook broader environmental factors, with local contexts frequently being the root causes. Understanding these contextual factors is crucial for effective improvements. This study aimed to explore ARH promotion based on the local knowledge of the Tengger people using a case study approach. Interviews were conducted with key stakeholders (n=2), parents (n=2), and adolescents (n=2). Results indicated that cultural and religious values are deeply integrated into ARH promotion. Four central foundations underpin these efforts: cultural identity, social control, harmony, and full participation. Cultural identity focuses on preserving and transmitting local traditions and values. Social control involves both structured community rules and unwritten norms that guide behavior. Harmony emphasizes maintaining balance and peace, crucial for collective well-being. Full participation ensures adolescents are engaged in community activities, fostering a sense of belonging and responsibility. These findings highlight the necessity of incorporating local cultural into ARH initiatives to enhance effectiveness. Aligning ARH promotion with the values and practices of the Tengger people can lead to better acceptance and sustainability of programs.